Rekonstruksi Pendidikan Islam Berbasis Tasawuf - Azzahra, Fatimah; Hasan, Gus Nafi Unnur; Mustafa, Labib; Ghifari, Reza Iqbal; Alfaraby, Figo Zulfan; Rosyidah, Amiliya Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to reconstruct an Islamic education paradigm grounded in Sufism as a response to the spiritual and moral crisis affecting contemporary education. In current practice, the spiritual dimension is often neglected due to the dominance of cognitive and materialistic approaches. This research uses a qualitative method through a literature study and applies Hans-Georg Gadamer’s hermeneutic analysis. The reviewed literature includes classical and contemporary works on Sufism, Islamic educational philosophy, and spiritual pedagogy. The findings reveal that core Sufi values such as repentance (taubah), patience (sabr), asceticism (zuhud), trust in God (tawakkul), and divine knowledge (ma’rifah) have significant potential in shaping spiritually grounded and ethically sound students. Integrating these values into the Islamic education curriculum can be achieved through thematic approaches, experiential learning, and reflective worship practices. Moreover, teachers are positioned not merely as instructors but as murabbi—spiritual guides who embody and model Sufi principles in daily life. This study recommends designing an Islamic education curriculum that is not only informative but also transformative, focusing on the inner development of holistic human beings (insan kamil).